Classification and Staging of Morgellons Disease: Lessons from Syphilis - Middelveen MJ; Martinez RM; Fesler MC; Sapi E; Burke J; Shah JS; Nicolaus C; Stricker RB (Dove Medical Press, 2020)
Marianne J Middelveen,1 Roberto M Martinez,2 Melissa C Fesler,3 Eva Sapi,4 Jennie Burke,5 Jyotsna S Shah,6 Carsten Nicolaus,7 Raphael B Stricker3 1Atkins Veterinary Services, Calgary, AB, Canada; 2Martinez Veterinary Services, Calgary, AB, Canada; 3Union Square Medical Associates, San Francisco, CA, USA; 4Department of Biology and Environmental Science, University of New Haven, West Haven, CT, USA; 5Australian Biologics, Sydney, NSW, Australia; 6IGeneX Laboratories, Palo Alto, CA, USA; 7BCA-Clinic, Augsburg, GermanyCorrespondence: Raphael B StrickerUnion Square Medical Associates, 450 Sutter Street, Suite 1504, San Francisco, CA 94108, USAEmail rstricker@usmamed.comIntroduction: Morgellons disease (MD) is a contested dermopathy that is associated with Borrelia spirochetal infection. A simple classification system was previously established to help validate the disease based on clinical features (classes I-IV).Methods: Drawing on historical and pathological parallels with syphilis, we formulated a more detailed staging system based on clinical features as well as severity of skin lesions and corresponding histopathological infection patterns, as determined by anti-Borrelia immunohistochemical staining.Results: Clinical classes I-IV of MD are further categorized as mild, moderate and severe, or stages A, B and C, respectively, based on histopathological findings. Stage A lesions demonstrated little or no immune infiltrates and little or no disorganization of cells; macrophages were not present, and hemorrhage was negligible. Extracellular isolated spirochetes and intracellular staining of keratinocytes in the lower epidermis was occasionally seen. Stage C lesions demonstrated positive staining of keratinocytes in the stratum basale and stratum spinosum and positive intracellular staining of macrophages for Borrelia. Aggregate Borrelia colonies were frequently encountered, hemorrhage was frequent, and intracellularly stained fibroblasts were occasionally seen. Stage B lesions demonstrated a pattern intermediate between Stages A and C.Conclusion: The enhanced staging system provides objective criteria to assess the severity of dermopathy in MD. Further studies are needed to determine the optimal treatment for MD based on this staging system related to Borrelia infection.Keywords: Morgellons disease, Lyme disease, Borrelia burgdorferi, relapsing fever Borrelia, tick-borne disease, syphilis, Treponema pallidum